Is D2 Lymphadenectomy Alone Suitable for Gastric Cancer With Bulky N2 and/or Para-Aortic Lymph Node Metastases After Preoperative Chemotherapy? - Xu, Wei; Liu, Wentao; Wang, Lingquan; He, Changyu; Lu, Sheng; Ni, Zhentian; Hua, Zichen; Zhu, Zhenglun; Sah, Birendra Kumar; Yang, Zhongyin; Zheng, Yanan; Feng, Runhua; et al. (Frontiers in Oncology, 2021)
For gastric cancer (GC) with extensive lymph node metastasis (bulky N2 and/or para-aortic lymph node metastases), there is no standard therapy worldwide. In Japan, preoperative chemotherapy (PCT) followed by D2 gastrectomy plus para-aortic lymph node dissection (PAND) is considered the standard treatment for these patients. However, in China, the standard operation for GC patients with only bulky N2 metastases was D2 gastrectomy. Besides, after PCT, whether doing PAND improves survival or not is debatable for GC patients with para-aortic lymph node (PAN) metastases. Therefore, we conducted this study to investigate whether D2 lymphadenectomy alone is suitable for these patients after PCT. Methods: We retrospectively collected data on patients from our electronic medical record system. GC patients with bulky N2 and/or PAN metastases who underwent D2 lymphadenectomy alone after PCT were enrolled. The survival outcomes and chemotherapy responses were analyzed and compared with the results of the JCOG0405 study. Results: From May 2009 to December 2017, a total of 83 patients met all eligibility criteria and were enrolled. The median survival duration for all patients was 40.0 months. The 3-year and 5-year OS rates for all patients were 50.3% and 45.6%, respectively. For patients with only bulky N2 metastasis, the 3-year and 5-year OS rates were 77.1% and 71.6%, respectively, which were similar to the results of the JCOG0405 study (82.7% and 73.4%). For patients with only PAN metastases, the 3-year and 5-year OS rates were 50.0% and 50.0%, respectively, which seemed to be lower than those of the JCOG0405 study (64.3% and 57.1%). For patients with bulky N2 and PAN metastases, the 3-year and 5-year OS rates were 7.4% and 0.0%, respectively, which were lower than those of the JCOG0405 study (20.0% and 20.0%). Conclusion: The results of our study suggest that D2 lymphadenectomy alone is suitable for GC patients with only bulky N2 metastasis after PCT. However, D2 lymphadenectomy alone perhaps is not suitable for patients with bulky N2 and PAN metastases after PCT.